2018
DOI: 10.1007/s11356-018-1688-9
|View full text |Cite
|
Sign up to set email alerts
|

Performance and efficiency of removal of pharmaceutical compounds from hospital wastewater by lab-scale biological treatment system

Abstract: The fate of pharmaceuticals after discharged from hospital into wastewater was clarified experimentally by using a new lab-scale conventional activated sludge (CAS) treatment reactor. The 43 target compounds belong to nine therapeutic classes (antivirals, antibacterials, anticancer drugs, psychotropics, antihypertensives, analgesic-antipyretics, contrast media, herbal medicines, and phytoestrogens) were selected with inclusion of 16 newly estimated compounds. The efficiency of the present reactor was estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Since high temperatures and strong solar irradiation were observed from May to September (Japan Meteorological Agency, 2017), it was considered that the pharmaceutical concentrations decreased due to microbial and solar decomposition in the summer season. However, previous research has shown that carbamazepine in sewage is hardly decomposed by bacteria (Nakada et al, 2007;Azuma et al, 2018) and that acetaminophen is hardly decomposed by sunlight (Kawabata et al, 2013), indicating that there are other reasons behind the seasonal variation in pharmaceutical concentrations. However, non-ionic surfactants and nonylphenols in Ayase River water during the non-irrigation season were reported to be higher than those during the irrigation season, and it was speculated that the reason for this was the decrease in agricultural wastewater discharge during the non-irrigated season (Yamazaki et al, 2000(Yamazaki et al, , 2001.…”
Section: Seasonal Variationmentioning
confidence: 95%
“…Since high temperatures and strong solar irradiation were observed from May to September (Japan Meteorological Agency, 2017), it was considered that the pharmaceutical concentrations decreased due to microbial and solar decomposition in the summer season. However, previous research has shown that carbamazepine in sewage is hardly decomposed by bacteria (Nakada et al, 2007;Azuma et al, 2018) and that acetaminophen is hardly decomposed by sunlight (Kawabata et al, 2013), indicating that there are other reasons behind the seasonal variation in pharmaceutical concentrations. However, non-ionic surfactants and nonylphenols in Ayase River water during the non-irrigation season were reported to be higher than those during the irrigation season, and it was speculated that the reason for this was the decrease in agricultural wastewater discharge during the non-irrigated season (Yamazaki et al, 2000(Yamazaki et al, , 2001.…”
Section: Seasonal Variationmentioning
confidence: 95%
“…The adsorption capacity decreased with increasing sludge aging [58] . Also, Azuma et al (2018) stated that the degradation of antiviral drugs in activated sludge is associated with log K d value which is the solid-water partition coefficient [81] .…”
Section: Antiviral Drugs Treatment Technologiesmentioning
confidence: 99%
“…However, its insufficient ability to eliminate anticancer drugs at STPs, as described above, necessitates the introduction of additional post-treatment technologies. Importance of such an advanced water treatment systems at STPs is becoming widely recognized [78][79][80], because of high power for removing not only PPCPs but also other chemicals such as EDCs [81], persistent organic pollutants (POPs) [82], bacterial pathogens, and viruses [83].…”
Section: Mass Balance Of Anticancer Drugsmentioning
confidence: 99%